BISNIS SEBAGAI KEKUATAN POLITIK: KAJIAN PENGEMBANGAN STRATEGI KOTA SURAKARTA DALAM PENGEMBANGAN INDUSTRI PARIWISATA (2005-2012) - Priyatno Harsasto (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
The rapid shift from centralised–authoritarian to decentralised–democratic rule in Indonesia has been accompanied by a large shift in sub-national government policies across districts. Based on  case study in Surakarta city comprising business surveys and  in-depth interviews, this report argues that demand-side pressures from local business and associations as well as supply-side pressures from local government leaders can be attributed as the broad explanation for the Surakarta city’s performance in tourism industry. In Indonesia’s early transition to democratic governance, business pressures have been constrained by collective action problems and perverse political incentives. On the other hand,  local government leaders with good vision, have strong powers and new incentives for policy reform. Local leaders have been playing crucial role in shaping political arena for business as well as civil society. In the name of political inclusion, they invite civil society as well business groups to involve in policy making process. This study’s findings suggest that government leadership is an important policy determinant that can shape the interests of business and the people. The ability of the leader to  create economic growth has been determinant in bridging the interests of business as well as the society as a whole.